The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0303-76572010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade, pressão e humilhação no trabalho: os trabalhadores e as novas fábricas de calçados no Ceará

Abstract: O objetivo deste artigo é mostrar o modo como as práticas organizacionais e a cultura dos locais de trabalho podem levar a experiências de humilhação e a situações constrangedoras no trabalho. A discussão baseia-se em entrevistas realizadas no decorrer de 2007, com 20 trabalhadores de três fábricas de calçados localizadas no Ceará. A análise de conteúdo das entrevistas indica que, apesar da humilhação e do constrangimento serem formas de violência conduzidas por indivíduos investidos de poder e autoridade na e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
2
0
5
Order By: Relevance
“…This paper suggests that stress coping strategies are developed by the footwear industries focused on workers' emotions and work problem solving (Folkman & Moskowitz, 2004), as these variables contribute to the relief of emotional distress, accepting responsibility, self-control, escape strategies and identification of specifics stressful (Folkman & Lazarus, 1988;Dardas & Ahmad, 2015). As for 'job dissatisfaction' changes in the organizational climate of footwear industries may reflect on important improvements in this factor (Rueda et al, 2012), since studies in this industrial sector have demonstrated the suffering experienced by workers (Borsoi et al, 2009;Rigotto et al, 2010;Silva et al, 2017). However, to initiate changes in companies, it would be necessary to have laws covering psychosocial risks, such as the Framework Directive 89/391/EEC; this declares that employers are obliged to ensure workers' health and to guarantee a safe and healthy work environment, both in terms of physical and psychosocial conditions at work (European Commission, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper suggests that stress coping strategies are developed by the footwear industries focused on workers' emotions and work problem solving (Folkman & Moskowitz, 2004), as these variables contribute to the relief of emotional distress, accepting responsibility, self-control, escape strategies and identification of specifics stressful (Folkman & Lazarus, 1988;Dardas & Ahmad, 2015). As for 'job dissatisfaction' changes in the organizational climate of footwear industries may reflect on important improvements in this factor (Rueda et al, 2012), since studies in this industrial sector have demonstrated the suffering experienced by workers (Borsoi et al, 2009;Rigotto et al, 2010;Silva et al, 2017). However, to initiate changes in companies, it would be necessary to have laws covering psychosocial risks, such as the Framework Directive 89/391/EEC; this declares that employers are obliged to ensure workers' health and to guarantee a safe and healthy work environment, both in terms of physical and psychosocial conditions at work (European Commission, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The literature contains several studies indicating that WRMDs affect almost every body part of workers in this industry, including the arm (Amano et al, 1988), the neck (Serratos-Perez & Mendiola-Anda, 1993), the shoulder (Descatha et al, 2004;Leclerc et al, 2004), the hand/finger (Gupta & Mahalanabis, 2006), the elbow (Descatha et al, 2007), the upper back (Aghili et al, 2012), the lower back (Warnakulasuriya et al, 2012), the knee (Dianat & Salimi, 2014), the hip/thigh and ankle/foot (Silva et al, 2016). In addition, the Brazilian footwear industry is marked by a history of physical and psychological violence perpetrated by supervisors against shop floor workers (Borsoi et al, 2009;Rigotto et al, 2010). Previous studies in footwear industries have evaluated the influence of few psychosocial factors in WRMDs or did not consider their impact on the various parts of the body.…”
mentioning
confidence: 99%
“…Em relação as indústrias de calçados, alguns estudos analisaram a influência de fatores psicossociais (ROQUELURE et al, 2002;BORSOI et al, 2009;RIGOTTO et al, 2010;AGHILI et al, 2012;DIANAT;SALIMI, 2014;FERNANDES et al, 2016;GONTIJO, 2017).…”
Section: Segundo O National Institute For Occupationalunclassified
“…É sugerido avaliação da organização dos postos de trabalho, visando a não manutenção de membros em posições desconfortáveis. Quanto a insatisfação com o trabalho, sugere-se realizar análise do clima e ambiente organizacional com atenção na carga de trabalho, relacionamentos com autoridade, metas de produção implementadas, exigências contraditórias e trabalho sobre pressão, visto que estudos mostram o sofrimento vivenciado por trabalhadores em indústrias calçadistas quando expostos a situações que envolvam tais fatores (BORSOI et al, 2009;RIGOTTO et al, 2010). Por fim, sugerese treinamentos e capacitações para os supervisores com o objetivo de melhorar o relacionamento com seus subordinados, aumentando a efetividade no monitoramento das operações, na habilidade de integração da equipe de trabalho e o "saber lidar" em situações conflitantes.…”
Section: Conclusãounclassified
“…Características relacionais como competitividade e rivalidade também foram muito citadas, contudo suas origens foram atribuídas aos modelos de gestão empregados pelas empresas. Em decorrência da "cultura do novo capitalismo", o espaço social das empresas estaria permeado pelo individualismo, pela incerteza e pela falta de responsabilidade nas relações sociais, como afirma Sennet (2006), citado por Camara et al 15 e por Rigotto et al 17 A responsabilidade das empresas foi apontada, seja por permitir práticas de assédio, seja por promovê-las, como ferramenta de gestão (assédio organizacional).…”
Section: Categoria Profissional Assediadaunclassified